Tradisi Primbon Perjodohan Aksara Jawa Honocoroko Dalam Prespektif Hukum Islam - Ubaidillah, M. Burhanuddin; Rochmatiq Azza, Nala; Muarrifatul Munisyah, Binti (JAS MERAH: Jurnal Hukum dan Ahwal al-Syakhsiyyah, 2025)
Primbon matchmaking constitutes a form of local wisdom that is still employed to determine the auspiciousness or inauspiciousness of marriage. In Javanese tradition, a life partner is regarded as part of the realm of mystery. It is believed that God conceals three matters: destiny (pesthi), one’s spouse (jodoh), and divine inspiration (wahyu). To attain insight into these matters, individuals traditionally undertake tirakat (spiritual discipline) through petung calculations based on the Javanese script Hanacaraka, which embodies philosophical meanings and mystical values derived from the sequence of letters and numerical symbolism. This tradition developed during the Majapahit era and was later reorganized during the period of Islamic rule in Java. This article focuses on the tradition of Primbon matchmaking based on the Javanese script Hanacaraka from the perspective of Islamic law. The discussion begins with an examination of the conception of the Javanese script Hanacaraka, followed by its philosophical significance in the journey of life and marital relations, the calculation patterns of Hanacaraka for prospective married couples, and the forms of spiritual adjustment employed when the Hanacaraka calculations are deemed incompatible. Through this analysis, the study seeks to reveal the essential nature of the Primbon matchmaking tradition of the Javanese script Hanacaraka within the framework of Islamic legal perspectives.